Ambientes de realidade virtual: novas possibilidades - Feliciano, Clayton Mendonça (2018)
Virtual reality (VR) and the forms of interactions with this environment have evolved and advanced a great deal in recent decades. Parallel to the advance of the creation and modeling of three-dimensional (3D) environments, new possibilities arise. Assuming that the virtual environment allows creating scenarios with details and architectural richness, the proposal of this work is focused on the development of a 3D environment and its application in the Web environment, having as object of study the Square Sé, Sao Paulo City. Bibliographical surveys were made to aggregate historical and cultural knowledge, as well as visits in locus for creation of the photographic collection and three-dimensional virtual development. The elaboration of the virtual scenario was made using Sketchup and Unity3D modeling software. Within what was proposed, both the modeling part and the integration part of the Web environment were successful